On Swing Pricing and Systemic Risk Mitigation - Malik, Sheheryar; Lindner, Peter (Washington, D.C. : International Monetary Fund, 2017)
Swing pricing allows a fund manager to transfer to redeeming or subscribing investors the costs associated with their trading activity, thus potentially discouraging large flows. This liquidity management tool, which is already used in major jurisdictions, may also help mitigate systemic risk. Here we develop and apply a methodology to investigate whether swing pricing does in fact help dampen flows out of funds, especially during periods of market stress. Drawing on evidence of first-mover advantage within a group of 'swinging' corporate bond funds, we provide policy considerations for enhancing the tool's effectiveness as a systemic risk mitigant.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet